2017
DOI: 10.1111/andr.12342
|View full text |Cite
|
Sign up to set email alerts
|

The great opportunity of the andrological patient: cardiovascular and metabolic risk assessment and prevention

Abstract: Andrologists, cardiologists and diabetologists (and general practitioners) have the great opportunity to collaborate and find shared clinical workup for the benefit of a large number of men. Several evidence established a link between erectile dysfunction (ED), cardiovascular disease (CVD), diabetes, and metabolic syndrome. Not only these conditions share many risk factors and pathophysiological mechanisms but also an emerging paradigm indicates that ED is, in fact, an independent marker of cardiovascular dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…1,[24][25][26][27] Moreover, impaired glucose transporter type 4 signaling in the myocytes, caused by an increase in some cytokines in the muscle tissue, 26,27 may be an additional mechanism to explain the dysfunctional In terms of hormonal changes, the chronic increase in testosterone levels observed in healthy athletes practicing mixed strength and endurance exercises 25 was assumed to be an additional beneficial conditioning effect that could lead to optimal muscle hypertrophy and function, improved sports performance and overall mood states, 17 increased metabolic rate (even at rest), 17 and enhanced metabolic pathways, as endogenous testosterone may improve glucose, lipid, and amino acid metabolism. 28 Conversely, OTS was associated with reduced testosterone, also previously described, 27 which may lead to impaired muscle recovery, decreased muscle mass, reduced basal metabolic rate, and less fat oxidation. 17 Estradiol has recently been shown to play beneficial roles in males with respect to bone mass, libido, humor, and body composition 29 when accompanied by a simultaneous increase in testosterone.…”
Section: Discussionmentioning
confidence: 74%
“…1,[24][25][26][27] Moreover, impaired glucose transporter type 4 signaling in the myocytes, caused by an increase in some cytokines in the muscle tissue, 26,27 may be an additional mechanism to explain the dysfunctional In terms of hormonal changes, the chronic increase in testosterone levels observed in healthy athletes practicing mixed strength and endurance exercises 25 was assumed to be an additional beneficial conditioning effect that could lead to optimal muscle hypertrophy and function, improved sports performance and overall mood states, 17 increased metabolic rate (even at rest), 17 and enhanced metabolic pathways, as endogenous testosterone may improve glucose, lipid, and amino acid metabolism. 28 Conversely, OTS was associated with reduced testosterone, also previously described, 27 which may lead to impaired muscle recovery, decreased muscle mass, reduced basal metabolic rate, and less fat oxidation. 17 Estradiol has recently been shown to play beneficial roles in males with respect to bone mass, libido, humor, and body composition 29 when accompanied by a simultaneous increase in testosterone.…”
Section: Discussionmentioning
confidence: 74%
“…2,3 Normative data obtained by studies on male population are urgently need for both DXA reference values and FRAX risk calculation in order to better tailor the diagnosis and the follow-up of men with osteoporosis. Andrological consultation performed in men with LOH represents an opportunity for male health 173 including bone. 4…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…At least four meta‐analyses have confirmed the relationship between arteriogenic ED and CV risk (Dong et al ., ; Yamada et al ., ; Fan et al ., ; Osondu et al ., ). All this evidence suggests that vasculogenic ED can be a harbinger for early CVD (Foresta et al ., ; Uddin et al ., ; Zhao & Zhang, ). A recent study observed that the effect of ED on future coronary risk was strongly affected by patient age.…”
Section: Introductionmentioning
confidence: 99%